O-43 RISK FACTORS FOR CANCER DEVELOPMENT IN PATIENTS WITH PRIMARY BILIARY CHOLANGITIS - Michelle Harriz Braga; Guilherme Grossi Lopes Cançado; Paulo Lisboa Bittencourt; Cláudia Alves Couto; Laura Vilar Guedes; André Mourão Costa Lima; Maria Lucia Gomes Ferraz; Cristiane Alves Villela-Nogueira; Jorge Nardelli Mateus; Luciana Costa Faria; Nathalia Mota De Faria Gomes; Maria Gomes Oliveira Elze; et al. (Annals of Hepatology, 2023)
Introduction and Objectives: Primary biliary cholangitis (PBC) and autoimmune hepatitis (AIH) and PBC overlap syndrome (AIH/PBC) have been associated with a higher risk of hepatocellular carcinoma (HCC) and extra-hepatic malignancy (EHM). This study aimed to assess potential risk factors associated with cancer development in PBC and AIH/PBC patients. Materials and Methods: The Brazilian Cholestasis Study Group database was reviewed and analyzed. Results: Among the 752 PBC patients enrolled, 64 of them with AIH/PBC, and 87 cancers were identified in 79 patients, including 20 cases of HCC and 67 of EHM. Patients with HCC had a higher prevalence of cirrhosis (95% vs. 32.5%, p= <0.001), smoking (55% vs. 12.3%, p= <0.001, CREST syndrome (30% vs. 7.6%, p= 0.003) and prior azathioprine (30% vs. 8%, p= 0.005) and prednisone (35% vs. 14%, p= 0.018) previous use, compared with their counterparts. Patients with EHM had a higher prevalence of smoking (42.3% vs. 12.3%, p= <0.001), AMA positivity (96.6% vs 80.6%, p = <0.001), azathioprine use (21% vs 8%, p= 0.01) and concurrent other autoimmune diseases. In multivariate analysis, cirrhosis, obesity and prior azathioprine therapy were independent risk factors for HCC, while Sjogren syndrome and psoriasis were associated with EHM. Fibrates reduced EHM risk. Conclusions: The prevalence of EHM is higher when compared to HCC in PBC patients. Cirrhosis, obesity, prior azathioprine use, and concurrent autoimmune diseases were significantly associated with cancer in PBC, while fibrate use was apparently protective against EHM.